AQP4-IgG autoimmunity in Japan and Germany: Differences in clinical profiles and prognosis in seropositive neuromyelitis optica spectrum disorders. Issue 2 (May 2021) - Asseyer, Susanna; Masuda, Hiroki; Mori, Masahiro; Bellmann-Strobl, Judith; Ruprecht, Klemens; Siebert, Nadja; Cooper, Graham; Chien, Claudia; Duchow, Ankelien; Schließeit, Jana; Liu, Jia; Sugimoto, Kazuo; et al.
Background: Clinical outcomes in neuromyelitis optica spectrum disorders (NMOSD) vary across different regions. Objective: To describe clinical profiles in Japanese and German NMOSD patients. Methods: Medical records of aquaporin-4-immunoglobulin G (AQP4-IgG) positive NMOSD patients from Japan (n = 54) and Germany (n = 38) were retrospectively analyzed. Results: The disability status was similar between both cohorts, although Japanese patients had a longer disease duration (13.3 ± 11.1 vs. 8.1 ± 6.9 years, p = 0.018) but similar relapse rates. Optic neuritis and myelitis were the most frequent attacks in both cohorts. Brain attacks occurred more frequently in Japanese patients (40.7% vs. 15.8%, p = 0.020). The time from disease onset (median [interquartile range] 2.3 [0.3-10.1] vs. 0.6 [0.2-1.9] years, p = 0.009) and the number of attacks (2.5 [1-7] vs. 2 [1-3], p = 0.047) until start of the first immunotherapy were higher in the Japanese cohort. Rituximab was the most common drug in the German cohort (52.6%) and not given in the Japanese cohort (p < 0.001), where oral prednisolone was the most common drug (92.6% vs. 15.8%, p < 0.001). The frequency of autoimmune comorbidities was higher in the German cohort (39.5% vs. 18.5%, p = 0.047). Conclusion: Compared with Japanese NMOSD patients, German patients presented with similar disability despite shorter disease duration and earlier and more frequent immunosuppressive therapy.